Comparative analysis of DC-DC converters for photovoltaic maximum power point tracking applications / \c Mustafa. M. Saleh Aburas. - Aburas, Mustafa. M. Saleh (School of Electrical System Engineering, Universiti Malaysia Perlis, 2017)
The primary project object is described as follow ; to design DC-DC converters for MPPT applications ; to develop and verify the DC-DC converters for MPP tracking application using MATLAB/Simulink ; to analyze and comparatively studies the performance of the converter in dealing with PV system environments in terms of efficiency and its tracking capability.